Educational Evaluation: Definition, Function, and General Requirements as a Pillar for Improving the Quality of Learning - Idris Afandi (Responsive: Jurnal Manajemen Pendidikan Islam, 2025)
Educational evaluation is an important component in the learning process that aims to determine the effectiveness and efficiency of educational activities. This article discusses in depth the definition of educational evaluation, the various functions inherent in it, and the general requirements that must be met so that evaluation can provide objective and useful results. Evaluation not only plays a role in assessing student learning outcomes, but also as a tool to improve the quality of the learning process, improve education programs, and assist decision-making by education stakeholders. In addition, in order for evaluation to have high validity and reliability, several general requirements are required, such as clarity of purpose, accuracy of evaluation tools, and the ability of evaluators to carry out the evaluation process. By understanding the basic concepts, functions, and general requirements of evaluation, educators and policy makers are expected to be able to implement evaluation more effectively in the context of formal education.